Development of Microfluidic Paper-Based Analytical Devices (µPADs) for Determination of Cd2+, Pb2+, and Cu2+ Ions in Mineral Water - Andri Hermansyah; Neil V. Rees; Jarnuzi Gunlazuardi; Rahmat Wibowo (Jurnal Kimia Sains dan Aplikasi, 2023)
Microfluidic paper-based analytical devices (µPADs) have been successfully developed using dual detection: electrochemical and colorimetric systems. The µPADs have the potential to be used as Pb(II), Cd(II), and Cu(II) sensors to test the quality of water. The fabrication process uses hot embossing and screen-printing methods. The working electrode in the electrochemical zone was enhanced by the bismuth metal deposition process, while in the colorimetric zone, the gold nanoparticles modified with thioctic acid and dansylhydrazine (TA-Au-DNS) were used as a colorimetric sensor to detect Cu. The basic material of µPADs was characterized using a Fourier-transform infrared (FTIR) and a contact angle meter (CAM). In the electrochemical zone, the signals of square wave anodic stripping voltammetry (SWASV) resulted in good detection of Pb(II) and Cd(II) (from 0 to 100 ppb) with a limit of detection of 1.588 and 1.42 ppb, respectively. In the colorimetric zone, the performance of TA-Au-DNS for detecting Cu metal was obtained from readings through the red-green-blue (RGB) sensor as a miniature of µPADs reader. The LOD, LOQ, and average Vx0 (linearity values) in the detection of Cu(II) (from 58 to 100 ppb) are 8.51 ppb, 28.36 ppb, and 0.41%, respectively.